Education Quality Assurance Monitoring - Thitapan, Phanthira; Kositpimanvach, Ekkarach (Journal of Graduate MCU KhonKaen Campus, 2023)
Quality monitoring of education, joint operational briefing session of the workersSuch as Academic Department, General Administration Department, Personal Administration Department, Budget Administration Department, Administrative Department. get a jobOther programs/activities or workshops, educational institutions should consider the details of each inspectionThe activities will then be jointly determined from the tonnage of which groups will investigate and prepare.CalendarMonitoring, monitoring, monitoring, evaluating and reporting quality monitoring resultsEducation. The purpose of monitoring the quality of education within the school is to provide personnel who are: In connection with the educational institutions, the implementation of the educational development plan of the educational institutions was informed.Clear. and will be used for continuous improvement and development as well as for public relations for related parties.be concerned with the resultsTo carry out the educational management development plan of the educational institution and to provide support and participation.The...Further development of quality of education. The institution will take the data to a conclusion as well as follow-up results for the previous year.Come on. (or information back 3 years) and prepared as information for use in improving operations.Work of A model of quality monitoring education may be presented in several ways, depending on the following: The purpose of the report is to report to a higher level of federal agencies?Keep reporting. Educational institutions may prepare a complete report if they want to publish it.Maybe report. In the form of pamphlets, newsletters, which are presented only to important issues in summary.take issue with Need a report or public relations, the school can choose the appropriate method ofthe context of eachEducational institutions, however, have five key points that should appear in the report as follows:This is the purpose. monitor the quality of education, the framework/the substance of monitoring the quality of educationmaintain a method Quality monitoring, quality monitoring, quality monitoring, recommendations to:Action. improve the quality of education